2018
DOI: 10.1080/11356405.2018.1462903
|View full text |Cite
|
Sign up to set email alerts
|

The role of executive functions in the relation between socioeconomic level and the development of reading and maths skills / El rol de las funciones ejecutivas en la relación entre el nivel socioeconómico y el desarrollo de habilidades lectoras y matemáticas

Abstract: Executive functions (EF) are a set of processes that allow individuals to plan, monitor and organize tasks and thus play a key role in the development of reading and maths skills. Environmental factors such as socioeconomic level (SEL) influence reading and maths skills as well as EFs. The aim of this study is to explore the extent to which executive functions play a mediating role between SEL and reading and maths performance. To this end, we assessed 286 Chilean primary education students: 86 with a high SEL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 63 publications
0
5
0
2
Order By: Relevance
“…Although both schools have similar characteristics, i.e., they are public (no fees) and non-profit, the Chilean and Belgium contexts could be quite different. Indeed, Chile has one of the highest income inequalities compared to other member countries of the Organization for Economic Cooperation and Development (OECD) and large differences in educational deprivation exist between children who come from high and low socio-economic status (SES; Escobar et al, 2018). Parents' occupation and their level of education have a high impact on children's behavior and attentional problems in 1st and 2nd grade children (Kalff et al, 2001).…”
Section: Context and Musical Experience Influencementioning
confidence: 99%
“…Although both schools have similar characteristics, i.e., they are public (no fees) and non-profit, the Chilean and Belgium contexts could be quite different. Indeed, Chile has one of the highest income inequalities compared to other member countries of the Organization for Economic Cooperation and Development (OECD) and large differences in educational deprivation exist between children who come from high and low socio-economic status (SES; Escobar et al, 2018). Parents' occupation and their level of education have a high impact on children's behavior and attentional problems in 1st and 2nd grade children (Kalff et al, 2001).…”
Section: Context and Musical Experience Influencementioning
confidence: 99%
“…De forma similar, Rosas, Espinoza, Garolera, y San-Martín (2017) encontraron que tanto las funciones ejecutivas como constructo global, así como la memoria de trabajo y la inhibición conductual de los niños de último año de educación parvularia predijeron sus habilidades académicas al finalizar el 1° grado escolar. Más aún, Escobar et al (2018) mostraron que el grado de inhibición de los niños es central para el rendimiento matemático, mediando la relación entre el nivel socioeconómico (NSE) y el rendimiento matemático en el 1° grado escolar.…”
Section: Investigaciones En Cognición Numérica En Chileunclassified
“…Similarly, Rosas, Espinoza, Garolera, and San-Martín (2017) found that both executive functions as a global construct, as well as working memory and behavioural inhibition of children in the last year of early childhood education, predicted their academic skills at the end of grade 1. Furthermore, Escobar et al (2018) showed that the degree of children's inhibition is central to mathematical performance, mediating the relation between socioeconomic status (SES) and mathematical performance in grade 1.…”
Section: Cognitive Mechanisms Underlying Mathematical Tasksmentioning
confidence: 99%
“…The relationship between EFs and academic performance has been widely documented in existing literature, and there is robust evidence indicating the influence of EFs on social-emotional and cognitive development at various stages of life [ 8 , 12 , 13 ]. A study investigating models demonstrated the predictive power of EF on reading and arithmetic performance two years later [ 14 ].…”
Section: Introductionmentioning
confidence: 99%